Effects of secukinumab on metabolic and liver parameters in plaque psoriasis patients. (10th October 2019) - Gerdes, S.; Pinter, A.; Papavassilis, C.; Reinhardt, M.
Abstract: Background: Psoriasis is associated with metabolic, liver and cardiovascular comorbidity. Secukinumab, a fully human monoclonal antibody that selectively neutralizes interleukin‐17A, has shown significant and sustained efficacy in the treatment of moderate to severe psoriasis. Objectives: This was an exploratory post hoc analysis of pooled data from three phase 3 studies in plaque psoriasis patient populations. The objective was to show the course of metabolic and liver parameters under secukinumab, etanercept or placebo treatment over time. A further objective was to assess the impact of selected comorbidities and metabolic characteristics on high‐sensitivity C‐reactive protein (hs‐CRP), as a surrogate marker of systemic inflammation. Methods: Data from the phase 3 randomized controlled trials [FIXTURE (NCT01358578), ERASURE (NCT01365455) and SCULPTURE (NCT01406938); n = 3010] were included in this analysis. Patients were treated with secukinumab 150 mg or 300 mg, placebo or etanercept 50 mg (FIXTURE only) as active comparator. A set of metabolic and liver parameters was longitudinally assessed over 52 weeks. Multivariate regression analyses assessed the impact of selected comorbidities and metabolic characteristics on hs‐CRP levels at baseline and under treatment. Results: Secukinumab treatment reduced hs‐CRP levels. Body weight and uric acid levels tended to decrease over 52 weeks with secukinumab. Secukinumab showed a neutral effect on fasting plasma glucose, lipid parameters and liver enzymes. Psoriatic arthritis, metabolic syndrome, obesity, impaired glucose metabolism, and hyperuricemia were each associated with increased hs‐CRP levels at baseline. Concomitant obesity attenuated the decline in hs‐CRP under treatment. Conclusions: These analyses suggest neutral to favourable long‐term trends in metabolic and liver parameters under secukinumab treatment. Metabolic comorbidities were associated with increased hs‐CRP levels, reflecting the role of systemic inflammatory processes in their pathophysiology.